TSC2 modulates cell adhesion and migration via integrin-α1β1 - Moir, Lyn M. (American Physiological Society, 2012)
Recent evidence suggests that the rare and progressive lung disease lymphangioleiomyomatosis (LAM) is metastatic in nature. Dysfunction of the tumor suppressor genes tuberous sclerosis complex (TSC), in particular mutational inactivation of TSC2, enhances both cell proliferation and migration. Although substantial progress has been made in understanding the role of TSC2 in abnormal LAM cell proliferation and its pharmacological targeting, the mechanisms underlying the enhanced migratory capacity in LAM are not well understood. In this study, we examined the role of TSC2 in cell attachment, spreading, and migration, processes that contribute to the metastatic phenotype. Here we show that loss of TSC2 increased both the attachment and spreading of mouse embryonic fibroblasts to the extracellular matrix proteins collagen type I and fibronectin and that reexpression of TSC2 reduced these effects. Integrin-α1β1 modulated cell migration with the β1-subunit involved in cell attachment and spreading as shown by using functional blocking antibodies. Loss of TSC2 increased integrin-α1 expression, and inhibition of this integrin subunit reduced cell migration. The enhanced attachment and spreading were independent of the intracellular signaling pathways mammalian target of rapamycin complex 1 and Rho-associated kinase, as pharmacological inhibition with rapamycin or Y27632, respectively, was without effect. Together, these data demonstrate that TSC2 controls cell migration, attachment, and spreading through the α1β1-integrin receptor and thus suggest a potential therapeutic target for the treatment of increased cell invasiveness in LAM.